Recognition and Restrictions on Minangkabau Customary Marriage Law in Overseas Practice - Fatih, Naufal Rakan; Rahmah, Nasywa Fauziyah; Valery, Chika Putri; Witaloka, Petrika Buwana (Rechtsvinding, 2025)
Minangkabau traditional marriage is a social system and customary law that regulates marital relations within the framework of matrilineal kinship. In the context of overseas communities, these customary practices face dynamics due to encounters with other cultures and the application of national law. This study aims to analyze the applicability of Minangkabau customary marriage law to the Nagari Padang Laweh community living in Tangerang by making Law Number 1 of 1974 concerning Marriage as the main legal basis. This study uses an empirical method with a sociological juridical approach, through the collection of field data from members of the Tangerang Padang Laweh Association (IKPL) and analysis of the marriage practices carried out. The results of the study show that Minangkabau marriage customs are still applied consistently if marriage is carried out among the Minangkabau tribe, especially in terms of marriage and the dominant role of the family of the woman. However, in intertribal marriages, the application of the custom tends to be abandoned and replaced by procedures that follow local customs or national laws. Based on Article 66 of the Marriage Law, customary law is still recognized as long as it does not conflict with the law and is still practiced by the community. Thus, this study concludes that the applicability of Minangkabau customary marriage law is conditional and is greatly influenced by the social context of overseas communities.